Oligocene-Miocene basin evolution in SE Anatolia, Turkey: constraints on the closure of the eastern Tethys gateway - Huesing, Silja K.; Zachariasse, Willem-Jan; van Hinsbergen, Douwe J. J.; Krijgsman, Wout; Inceoez, Murat; Harzhauser, Mathias; Kroh, Andreas (Geological Soc Publishing House, 2009)
The Oligocene-Miocene was a time characterized by major climate changes as well as changing plate configurations. The Middle Miocene Climate Transition (17 to 11 Ma) may even have been triggered by a plate tectonic event: the closure of the eastern Tethys gateway, the marine connection between the Mediterranean and Indian Ocean. To address this idea, we focus on the evolution of Oligocene and Miocene foreland basins in the southernmost part of Turkey, the most likely candidates to have formed this gateway. In addition, we take the geodynamic evolution of the Arabian-Eurasian collision into account. The Mus and Elazig basins, located to the north of the Bitlis-Zagros suture zone, were most likely connected during the Oligocene. The deepening of both basins is biostratigraphically dated by us to occur during the Rupelian (Early Oligocene). Deep marine conditions (between 350 and 750 m) prevailed until the Chattian (Late Oligocene), when the basins shoaled rapidly to subtidal/intertidal environment in tropical to subtropical conditions, as indicated by the macrofossil assemblages. We conclude that the emergence of this basin during the Chattian severely restricted the marine connection between an eastern (Indian Ocean) and western (Mediterranean) marine domain. If a connection persisted it was likely located south of the Bitlis-Zagros suture zone. The Kahramanmaras basin, located on the northern Arabian promontory south of the Bitlis-Zagros suture zone, was a foreland basin during the Middle and Late Miocene, possibly linked to the Hatay basin to the west and the Lice basin to the east. Our data indicates that this foreland basin experienced shallow marine conditions during the Langhian, followed by a rapid deepening during Langhian/Serravallian and prevailing deep marine conditions (between 350 and 750 m) until the early Tortonian. We have dated the youngest sediments underneath a subduction-related thrust at c. 11 Ma and suggest that this corresponds to the end of underthrusting in the Kahramanmaras, region, i.e. the end of subduction of Arabia. This age coincides in time with the onset of eastern Anatolian volcanism, uplift of the East Anatolian Accretionary Complex, and the onset of the North and East Anatolian Fault Zones accommodating westward escape tectonics of Anatolia. After c. 11 Ma, the foreland basin south of the Bitlis formed not (or no longer) a deep marine connection along the northern margin of Arabia between the Mediterranean Sea and the Indian Ocean. We finally conclude that a causal link between gateway closure and global climate change to a cooler mode, recorded in the Mi3b event (delta O-18 increase) dated at 13.82 Ma, cannot be supported.
Keywords: Planktonic Foraminiferal Biostratigraphy; Paleoclimatic Interpretation; Integrated Stratigraphy; Isotope Stratigraphy; Southern Neotethys; Neogene Evolution; Ocean Circulation; Stable-Isotopes; Middle; Plate